Comparison of Polysomnographic and Portable Home Monitoring Assessments of Obstructive Sleep Apnea in Saskatchewan Women - JA Gjevre; RM Taylor-Gjevre; R Skomro; J Reid; M Fenton; D Cotton (Canadian Respiratory Journal)
OBJECTIVES: To compare a commercially available, level III in-home diagnostic sleep test (Embletta, Embletta USA) and in-laboratory polysomnography (PSG) in women with suspected obstructive sleep apnea (OSA).